2023
DOI: 10.1007/s00018-023-04824-6
|View full text |Cite
|
Sign up to set email alerts
|

Activity-dependent regulation of the BAX/BCL-2 pathway protects cortical neurons from apoptotic death during early development

Abstract: During early brain development, homeostatic removal of cortical neurons is crucial and requires multiple control mechanisms. We investigated in the cerebral cortex of mice whether the BAX/BCL-2 pathway, an important regulator of apoptosis, is part of this machinery and how electrical activity might serve as a set point of regulation. Activity is known to be a pro-survival factor; however, how this effect is translated into enhanced survival chances on a neuronal level is not fully understood. In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…Bc12 is also involved in the regulation of neural differentiation, as overexpression of Bc12 can promote cell differentiation towards a neural lineage 14 , 34 . Studies on cerebral ischemia in rats have shown that overexpression of Bc12 not only improves the survival of cortical neurons 35 , but also significantly promotes the differentiation of transplanted embryonic stem cells into nerve cells, leading to enhanced functional recovery 34 . Furthermore, Bc12 plays a key role in axon growth and regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Bc12 is also involved in the regulation of neural differentiation, as overexpression of Bc12 can promote cell differentiation towards a neural lineage 14 , 34 . Studies on cerebral ischemia in rats have shown that overexpression of Bc12 not only improves the survival of cortical neurons 35 , but also significantly promotes the differentiation of transplanted embryonic stem cells into nerve cells, leading to enhanced functional recovery 34 . Furthermore, Bc12 plays a key role in axon growth and regeneration.…”
Section: Discussionmentioning
confidence: 99%